Pendampingan Guru Sekolah Menengah Kejuruan Dalam Strategi Pembelajaran Administrasi Perkantoran Berbasis Kebutuhan Industri - Ardian Ridwanca (CV. ITTC INDONESIA, 2026)
In the author's article, discussing the dynamic development of industry requires vocational high school graduates to have office administration competencies according to the needs of the world of work. However, there is a gap between learning in schools and industry demands, especially in the use of office technology, digital document management, business communication, and professional work culture. In this community service activity, the author aims to improve the competency of vocational high school teachers majoring in Office Administration at the Central Java Provincial Level in order to design learning strategies based on DUDI needs. The method used is descriptive qualitative with a participatory mentoring model through the stages of needs identification, training, implementation, and evaluation. Data were collected through observation, interviews, documentation. The delivery of material in front of the teachers showed results of 40% very satisfied, 50% satisfied, 5% quite satisfied, and 5% sufficient. This shows that the material delivered to the teachers is very relevant in today's industrial world. And also what is expected includes improving teacher competency, the form of project-based learning strategies, problem-based learning, teaching factories, the creation of industry-based learning models, and the establishment of collaboration between schools and DUDI.